Factors related to completion of referral among women with suspected cervical cancer and dysplasia in Tanzania. Issue 1 (17th November 2020) - Yim, Elizabeth T.; Rogers, Taylor B.; Msami, Khadija; Calixte, Rose; Kahesa, Crispin; Mwaiselage, Julius D.; Dorn, Joan; Soliman, Amr S.
Abstract: Objective: To investigate completion of referral among women with suspected cervical cancer in Tanzania. Methods: Retrospective cohort study of 196 women referred from two healthcare clinics to Ocean Road Cancer Institute, Dar es Salaam, between March 2016 and June 2018. Women with precancerous lesions or suspected cancer were interviewed about their knowledge and perception of cervical cancer and referred for follow‐up. Results: Most participants were unable to name symptoms (55.1%), prevention methods (88.3%), or treatments (59.0%), although 79.1% rated the disease as severe. Women who came for routine early detection were less likely to complete referral than those who did not (odds ratio [OR], 0.18; 95% confidence interval [CI], 0.05–0.70). Women who knew someone who died from cervical cancer were 5.40 times more likely to complete referral than those who did not. Knowing someone with cervical cancer was a predictor of referral completion in three multivariate models: OR, 5.62 (95% CI, 2.20–14.38); 4.34 (1.64–11.47); and 4.61 (1.72–12.36). Having severe symptoms was a predictor of non‐completion in two models: 0.30 (0.12–0.75) and 0.35 (0.14–0.87). Conclusion: Patient‐directed interventions should include education involving survivors of cancer and dysplasia, whereas system‐directed interventions should utilize reminders to increase referral completion. Abstract : Factors related to failure to complete referral for early detection of cervical cancer among women in Tanzania include lack of knowledge and inconsistent referral instructions.